Poder e gênero em Miguel Ángel Asturias, Érico Verissimo e Gioconda Belli - Oliveira, Amanda da Silva (2015)
This dissertation aims to study power and genre in three Latin American novels: Mister President, by Miguel Ángel Asturias, His Excellency, the Ambassador, by Erico Verissimo and A women’s country, by Gioconda Belli. Dealing with the definition of concepts of the literary field of Guatemala, Brazil and Nicaragua, from the year of publication of the analyzed works, the textual analyses are directed towards the perception of the way power stablishes itself under the form of dictatorship oppression in Latin America, and how female characters are presented in these narratives according to this oppression. There is also the identification of the speeches of possible worlds of equality and social justice in Latin America, as produced by the authors.